Intraparotid mucous retention cyst in an infant: a rare case report. Issue 8 (October 2020) - Solano, N.; Castro, B.; Perez, L.; Ramos, S.; Peraza, A.
Abstract: Mucocoeles can be defined as benign lesions that have resulted from extravasation or retention of saliva in the extraglandular spaces, and commonly affect the minor salivary glands. This case details a mucous retention cyst within the parotid gland of an infant, and its management.